Implementation of Taxation Data Integration in State-Owned Enterprises to Strengthen Good Corporate Governance - Prianto Budi Saptono; Dwi Purwanto (Politeknik Negeri Bengkalis, 2021)
This study aims to analyze the taxation data integration within the State-Owned Enterprises (BUMN) in strengthening Good Corporate Governance (GCG). This study is descriptive with a qualitative method and uses a content analysis approach. The authors conducted the study by doing a review of the literature on GCG and taxation. The literature comes from books, journals, regulations, policies, electronic sources, the internet, previous research results, press releases, and newspapers. The result of this study suggest that the taxation data integration within BUMN is an essential innovation means of improving corporate governance. The taxation data integration program will indirectly make it easier for BUMN to meet their tax rights and obligation. Additional benefits of tax governance include lowering the likelihood of disputes occurring and avoiding long audit processes, which both lower taxpayer compliance costs and lessen the likelihood of potential disputes.